Peningkatan Pendapatan GAPOKTAN Melalui Diversifikasi Berbasis Olahan Jagung - Vivi Nuraini; Onne Akbar Nur Ichsan; Lianda Novias Sholihah; Retna Indri Juwita (Jurnal Pengabdian kepada Masyarakat UBJ, 2023)
Abstract GAPOKTAN Wonosegoro is one of the GAPOKTANs of Cepogo Village which produces cassava, chayote and corn. One of the problems that is often faced by GAPOKTAN is the decrease in the price of crops when the harvest is abundant, even though the shelf life of these commodities is not long lasting. The selling price of agricultural products during the main harvest experienced a very significant decrease. For this reason, it is necessary to process agricultural products into finished products. Diversification of processed corn is one of the solutions for increasing sales value, increasing shelf life and indirectly increasing the profits of the Association of Farmers Groups (GAPOKTAN). The purpose of this community service is to reduce the sale of raw agricultural products to finished products. Processing, packaging and marketing training is expected to be a solution to existing problems. The expected outcome of this service is that GAPOKTAN Wonosegoro is able to process and sell corn-based food products in collaboration with BUMDesa Tumang as a distributor so that they can improve shared welfare. Keywords: Diversification , Corn, GAPOKTAN